Physical and mechanical assessment of Itauba wood welded by rotary friction - Costa Viana, Ana Carolina; Barbosa Sampaio, Renato; Dias de Moraes, Poliana; Lindolfo Weingaertner, Walter (Maderas. Ciencia y Tecnología, 2025)
Rotary friction welding is a rapid and sustainable wood joining method, which eliminates the need for conventional adhesives or mechanical fasteners. Its application to Brazilian tropical hardwoods like itauba remains largely unexplored. The absence of established welding parameters for itauba-itauba (dowel-substrate) joints leads to unpredictable mechanical performance, limiting the industrial viability of this technique. This exploratory research aimed to evaluate the physical characteristics of the welded interface using scanning electron microscopy and assessed the influence of pre-drilled hole stage (one- and two-stage) and feed rate (300 mm/min, 400 mm/min, and 500 mm/min) on the mechanical performance of itauba welded joints. The ultimate objective was to determine the optimal welding parameters. The results demonstrate that the dowel wood fibers were covered by softened intercellular material, forming a smooth and uniform surface. The average taper rate of the dowels, from 3,72 % to 5,39 %, was influenced by the pre-drilled hole stage. The highest taper rates were obtained for two-stage pre-drilled holes, in which piece A had a smaller diameter (7 mm). Tensile testing demonstrated that specimens with a one-stage pre-drilled hole exhibited higher maximum pull-out loads than those with two-stages. The highest average shear strength, 1,21 MPa, was obtained for 1-stage pre-drilled hole and 300 mm/min or 400 mm/min of feed rate.